Effect of hydroxyethyl starch on bleeding after cardiopulmonary bypass: a meta-analysis of randomized trials - Navickis, Roberta J; Haynes, Gary R; Wilkes, Mahlon M (The Journal of thoracic and cardiovascular surgery, 2012)
The effects of hydroxyethyl starch on bleeding after cardiopulmonary bypass were determined. A meta-analysis was performed of postoperative blood loss in randomized clinical trials of hydroxyethyl starch versus albumin for fluid management in adult cardiopulmonary bypass surgery. Impacts of hydroxyethyl starch molecular weight and molar substitution were assessed. Randomized trials directly comparing different hydroxyethyl starch solutions were also included. Eighteen trials with 970 total patients were included. Compared with albumin, hydroxyethyl starch increased postoperative blood loss by 33.3% of a pooled SD (95% confidence interval, 18.2%-48.3%; P < .001). Risk of reoperation for bleeding was more than doubled by hydroxyethyl starch (relative risk, 2.24; 95% confidence interval, 1.14-4.40; P = .020). Hydroxyethyl starch increased transfusion of red blood cells by 28.4% of a pooled SD (95% confidence interval, 12.2%-44.6%; P < .001), of fresh-frozen plasma by 30.6% (95% confidence interval, 8.0%-53.1%; P = .008), and of platelets by 29.8% (95% confidence interval, 3.4%-56.2%; P = .027). None of these effects differed significantly between hydroxyethyl starch 450/0.7 and 200/0.5. Insufficient data were available for hydroxyethyl starch 130/0.4 versus albumin; however, no significant differences were detected in head-to-head comparisons of hydroxyethyl starch 130/0.4 with 200/0.5. Albumin improved hemodynamics. There were no differences in fluid balance, ventilator time, intensive care unit stay, or mortality. Hydroxyethyl starch increased blood loss, reoperation for bleeding, and blood product transfusion after cardiopulmonary bypass. There was no evidence that these risks could be mitigated by lower molecular weight and substitution.